Estimates of the coherent leakage of sound from an ocean surface duct - Jones, Adrian; Duncan, Alec; Zhang, Z. (2016)
For underwater sound transmission in a mixed-layer surface duct, the trapping of sound and the coherent leakage of some of this energy from the duct are well known phenomena. Models of sound transmission which include wave effects, such as modal models or Parabolic Equation models, include implicit determinations of the rates of coherent leakage. However for some applications it is useful or instructive to obtain direct analytic determinations of the leakage. Work carried out by the authors on the derivation of an approximate algorithm for the rate of coherent duct leakage is presented, along with comparisons with leakage rates determined by a wave-type model for several surface duct scenarios.